Menggali Maskulinitas Analisis Rekonstruksi KAHF untuk Pemasaran yang Efektif - Azhari, Rafika; Sazali, Hasan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The study discusses how to communicate masculinity as well as the urgent need to reconstruct the understanding of masculinities in a marketing context that is more inclusive and relevant to the current era. The study highlighted the importance of diversification in the representation of masculinity in marketing, by showing that campaigns that promote diversity in representation tend to receive positive feedback from consumers, leading to increased attachment and loyalty. The research method involves phenomenological analysis of the phenomena of various social media and E-Commerce Kahf in marketing its products. This research aims to identify concrete strategies in doing product marketing. The findings of this research are expected to provide in-depth insight into Kahf's reconstruction in doing marketing with the guise of masculinity.